1980
DOI: 10.1212/wnl.30.7.732
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile myasthenia gravis

Abstract: We studied 32 children with myasthenia gravis over a period of 12 years. The mean age at onset was 7.7 years. Presentation was ocular in 63% of patients. Another major disease in addition to myasthenia occurred in 44% of patients; a seizure disorder was the most commonly associated disease. Serum IgG antibody to nicotinic acetylcholine receptor was present in 53% of patients and did not correlate with severity of disease or treatment. Medical management was effective in 63%; thymectomy was effective in only 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
45
2
4

Year Published

1983
1983
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 0 publications
7
45
2
4
Order By: Relevance
“…ities (Hokkanen and Toivakka 1969; Kazis et al 1984), transient neurological signs (Patten 1978;Shintani et al 1989) and epilepsy (Hoefer et al 1958; Snead et al 1980) have been reported, which suggest the involvement of the central nervous system (CNS). However, psychiatric disturbances have been described only in sporadic case reports (Oosterhuis and Wilde 1964; Gittleson and Richardson 1973; Musha et al 1981; Ananth et al 1984).…”
mentioning
confidence: 99%
“…ities (Hokkanen and Toivakka 1969; Kazis et al 1984), transient neurological signs (Patten 1978;Shintani et al 1989) and epilepsy (Hoefer et al 1958; Snead et al 1980) have been reported, which suggest the involvement of the central nervous system (CNS). However, psychiatric disturbances have been described only in sporadic case reports (Oosterhuis and Wilde 1964; Gittleson and Richardson 1973; Musha et al 1981; Ananth et al 1984).…”
mentioning
confidence: 99%
“…Serum acetylcholine receptor antibodies (AchR Ab) are important to confirm the diagnosis but are more frequently negative when compared to adults. Antibody-negative myasthenia gravis were not rare in children [3][4][5] . We diagnosed this child based on clinical and neostigime test, but we could not do AchR auto antibodies level which was our limitation.…”
Section: Discussionmentioning
confidence: 93%
“…Myasthenia gravis (MG) in childhood and adolescence is rare comprising 10 to 20 % of all myasthenic patients 2,3 . Myasthenia gravis is a chronic disease characterized by rapid fatigability of striated muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os casos em crianças e adolescentes respondem por 11 a 24% de todos os pacientes com miastenia gravis e podem ser divididos em neonatal, congênita e juvenil (3,6) . A miastenia gravis neonatal é uma desordem transitória, que pode afetar crianças nascidas de mães com miastenia gravis, e é causada pela passagem transplacentária de anticorpos IgG contra o receptor de acetilcolina.…”
Section: I S C U S S ã Ounclassified